Overview of Midwives' Attitudes Regarding Loving Care for Mothers During Childbirth at Partner Clinics School St. Elisabeth College of Health Sciences Medan2025 - Aprilita Br Sitepu; Asnita Rouli Simanjuntak; Ermawaty Siallagan; Desriati Sinaga (PT. Padang Tekno Corp, 2026)
The maternal mortality rate in Indonesia remains a serious issue, primarily due to the lack of quality childbirth services. One approach applied is the loving care for mothers, which is a service approach that respects the rights, comfort, and wishes of mothers during the childbirth process. Research objective: To understand the attitudes of midwives regarding loving care for mothers during childbirth. Research method: This type of research is descriptive. The research locations are Lidya Clinic, Katarina Clinic, Kasih Bunda Clinic, Pratama Bertha Clinic, Pratama Romauli Clinic. Research results: The results indicate that 21 respondents (70%) have a positive attitude, while 9 respondents (30%) have a negative attitude. Conclusion: Based on the research results, it shows that midwives have a positive attitude to awards maternal affection care during labor. The researchers suggest that midwives at Collaborative Clinics of Santa Elisabeth Health Sciences College Medan should maintain their positive attitude in providing services